A Closed-Loop Supply Chain with Trade-In Strategy under Retail Competition. (18th January 2018) - Huang, Yanting
Abstract : This paper investigates a closed-loop supply chain (CLSC) consisting of a manufacturer and two competing retailers who collect used products through trade-in strategy. Three remanufacturing models with trade-in strategy have been developed: ( 1 ) the manufacturer implements trade-in strategy (Model M), ( 2 ) single retailer collects used products through trade-in strategy (Model SR), and ( 3 ) two retailers undertake trade-in activities (Model TR). We analyze the impact of trade-in strategy on equilibrium decisions and chain members' profits when retailing is competitive. We show that, as for the manufacturer, he prefers the case where trade-in is implemented by himself due to the direct benefits from remanufacturing, and the case of single retailer implementing trade-in strategy is the most unfavorable for the environment. We also show that, if the net value of a used product is sufficiently large, the retailer only selling products benefits from the case of the manufacturer implementing trade-in strategy because the manufacturer can coordinate both the forward and reverse flows, and Model M dominates Model TR for the retailer who undertakes both product sales and trade-in strategy. Moreover, a larger trade-in rebate can be achieved when two retailers simultaneously conduct trade-in strategy due to the intense competition between two retailers.